2021
DOI: 10.3390/ijerph18179216
|View full text |Cite
|
Sign up to set email alerts
|

Combined Multimorbidity and Polypharmacy Patterns in the Elderly: A Cross-Sectional Study in Primary Health Care

Abstract: (1) Background: The acquisition of multiple chronic diseases, known as multimorbidity, is common in the elderly population, and it is often treated with the simultaneous consumption of several prescription drugs, known as polypharmacy. These two concepts are inherently related and cause an undue burden on the individual. The aim of this study was to identify combined multimorbidity and polypharmacy patterns for the elderly population in Catalonia. (2) Methods: A cross-sectional study using electronic health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Interestingly, at the lifestyle behavior layer, our study found that a low medication adherence was a risk factor, while a moderate medication adherence was a protective factor for developing multimorbidity. The former was consistent with previous views [ 56 ], while the latter was probably due to our data being cross-sectional and could not determine causality between the variables, whereas older people with a high medication adherence tended to be those who were already suffering from disease or even multimorbidity [ 57 ], which is consistent with Domino’s study, which concluded that there was a lower non-adherence among patients with multimorbidity [ 58 ]. Older adults with lower levels of physical activity are more likely to suffer from multimorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, at the lifestyle behavior layer, our study found that a low medication adherence was a risk factor, while a moderate medication adherence was a protective factor for developing multimorbidity. The former was consistent with previous views [ 56 ], while the latter was probably due to our data being cross-sectional and could not determine causality between the variables, whereas older people with a high medication adherence tended to be those who were already suffering from disease or even multimorbidity [ 57 ], which is consistent with Domino’s study, which concluded that there was a lower non-adherence among patients with multimorbidity [ 58 ]. Older adults with lower levels of physical activity are more likely to suffer from multimorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the enrolled samples was about 75 years, except for the work of McCracken et al [ 21 ], performed on older patients (mean age 85 years). Concerning the definition of polypharmacy, four studies considered the usual consumption of 5 or more medications per day [ 13 , 14 , 18 , 20 , 22 ], two studies of > 5 drugs/ day [ 17 , 19 ], one of ≥ 4 drugs/day [ 4 ], and one of ≥ 9 drugs per day [ 21 ]. One work reported the median number of medications taken, but not the frequency of polypharmacy [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several works have shown that the frequency of polypharmacy increases with advancing age [ 3 , 4 ], in parallel with the accumulation of chronic diseases [ 5 ]. In this context, the interactions between multiple drugs and diseases can lead to more challenging management and control of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the concept of polypharmacy, four studies [9][10][11][12][13] looked at the typical intake of five or more medications per day, two studies 14,15 looked at more than five, one study 16 looked at less than four, and one looked at more than nine drugs per day. 17 In this prospective observational study, we evaluated the effects of T2DM on the number of medications administered to diabetic patients older than 40 years old as well as the effects of polypharmacy on diabetic patients.…”
Section: Discussionmentioning
confidence: 99%